Short versus long course of colistin treatment for carbapenem-resistant A. baumannii in critically ill patients: A propensity score matching study - Wasan Katip; Ajaree Rayanakorn; Peninnah Oberdorfer; Puntapong Taruangsri; Teerapong Nampuan (Elsevier, 2023)
Background: Carbapenem-resistant Acinetobacter baumannii (CRAB) is one of the most commonly found nosocomial infections in critically ill patients. However, the appropriate treatment period for a specific group of critically ill patients with CRAB infection is currently being debated. Therefore, our study aimed to evaluate the optimal courses of therapy for critically ill patients with CRAB infection by comparing the outcomes of colistin therapy of short duration (<14 days) versus long duration (≥ 14 days). Methods: A retrospective cohort study was conducted at Nakornping Hospital on critically ill patients with CRAB infection who received either a short or long course of colistin treatment between 2015 and 2022. The primary outcome was the 30-day mortality rate while secondary outcomes were clinical response, microbiological response, and nephrotoxicity. Propensity score matching with a 1: 1 ratio was performed to reduce potential biases. Furthermore, a logistic regression model was used to estimate the odds ratio (OR). Results: A total of 374 patients met the inclusion criteria. Two hundred and forty-eight patients were recruited after utilizing propensity scores to match patients at a 1: 1 ratio. The results from the propensity score matching analysis demonstrated that the long-course therapy group had a lower 30-day mortality rate compared to the short-course therapy group (adjusted OR (aOR) = 0.46, 95% CI: 0.26-0.83, p = 0.009). The clinical response and microbiological response rates were higher in patients who received the long course of colistin therapy compared to those receiving the short course (aOR = 3.24, 95% CI: 1.78-5.92, p = 0.001; aOR = 3.01, 95% CI: 1.63-5.57, p = 0.001). There was no significant different in the occurrence of nephrotoxicity (aOR = 1.28, 95% CI: 0.74-2.22, p = 0.368) between the two treatment groups. Conclusion: A long course of colistin therapy resulted in a lower 30-day mortality rate in critically ill patients, and better clinical and microbiological outcomes, but similar nephrotoxicity as compared to a short course of colistin therapy. Therefore, a specific subset of critically ill patients who had CRAB infection needed to be considered for a long course of therapy.